2018
DOI: 10.1080/24749508.2018.1525671
|View full text |Cite
|
Sign up to set email alerts
|

Population structure and regeneration status of rhododendrons in temperate mixed broad-leaved forests of western Arunachal Pradesh, India

Abstract: This study was conducted to investigate the population structure and regeneration status of Rhododendron tree species in temperate mixed broad-leaved forests in Tawang and West Kameng districts of western Arunachal Pradesh, India. Population structure was determined through densities of seedlings, saplings and adults from the sampling quadrats. Based on density of individuals at the seedling, sapling and adult, the regeneration status of the species was determined. Density and basal area of the selected rhodod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 94 publications
0
19
0
Order By: Relevance
“…The high number of seedlings also indicates that this species is possible to be developed as a commodity traded on a large scale in the future. The population structure of G. versteegii in this forest can be classified to have "good regeneration" based on the ecological principles of forest structure, because it has the structure of seedling > sapling > adult (Paul et al 2019). The population structure of G. versteegii in Nggalak Forest is quite different and better in terms of plant regeneration compared to the structure in Pongkor, Flores that showed higher sapling stage than the seedling stage (Rindyastuti et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The high number of seedlings also indicates that this species is possible to be developed as a commodity traded on a large scale in the future. The population structure of G. versteegii in this forest can be classified to have "good regeneration" based on the ecological principles of forest structure, because it has the structure of seedling > sapling > adult (Paul et al 2019). The population structure of G. versteegii in Nggalak Forest is quite different and better in terms of plant regeneration compared to the structure in Pongkor, Flores that showed higher sapling stage than the seedling stage (Rindyastuti et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…But if we consider the density of saplings of 1240 per hectare in the present study which lies between 800 and 2000 saplings per hectare, the forest has fair regeneration capacity as per Community Forestry Inventory Guidelines (MFSC 2002). Paul et al (2019) revealed that about 77% of the species demonstrated fair regeneration, 8% species indicated good regeneration while 15% of the species displayed no regeneration in a study of the population structure and regeneration status of Rhododendron tree species in temperate mixed broad-leaved woodlands in Tawang and West Kameng regions of western Arunachal Pradesh, India. A population with a sufficient number of seedlings, saplings and young trees depicts satisfactory regeneration behavior, while the deficient number of seedlings and saplings of the species in woodland demonstrates poor regeneration and the total non-attendance of seedlings and saplings of tree species in a forest shows no regeneration (Pokhriyal et al 2010).…”
Section: Regeneration Status Of Panchase Forestmentioning
confidence: 99%
“…Relative abundance and growth forms of currently dominant species are the indicators of future community structure in the forest. Proportions of seed-lings, saplings and juvenile trees are greatly influenced by the presence of mature trees and abiotic (natural and unnatural) resources (Paul et al 2019). The results obtained from the present study revealed the seedling dynamics of Murree in terms of species richness, diversity level and equitability in the forest along with the present and expected conditions in future.…”
Section: Discussionmentioning
confidence: 54%
“…Ahmed et al (2006) found the Pinus wallichiana and Pinus roxburghii community at this elevation from Himalayan ranges, and they concluded (Ahmed et al 2006;Siddiqui 2011;Ahmed, Shaukat 2012) that could ensure seed production in the forest, whereas the present studies of disturbed forests showed the lowest number of seedlings and the lowest representatives of mature seed-bearing trees (Khan et al 2018a, b;Khan 2020). Paul et al (2019) concluded that the habitat destruction was a consequence for alteration in the population structure of Rhododendron spp. dominated temperate forest in Arunachal Pradesh, India.…”
Section: Discussionmentioning
confidence: 57%